SHIFTING FOCUS: THE ROLE OF ENVIRONMENTAL, SOCIAL, AND GOVERNANCE FACTORS IN INVESTMENT POLICY DURING A PANDEMIC - Serghei PETIGHIN (Eastern European Journal of Regional Studies)
This paper investigates the importance of Environmental, Social, and Governance (ESG) factors in investment policy during the COVID-19 pandemic and their contribution to long-term resilience and sustainability. By conducting a comprehensive literature review based on peer-reviewed articles, financial institution reports, and government policies, this study examines the financial resilience of ESG-oriented investments during the pandemic, the integration of ESG factors in investment policy, and post-pandemic trends in ESG investing. The paper also explores the role of ESG factors in fostering long-term resilience and sustainability and discusses challenges and opportunities for ESG investing during and after the pandemic. The findings suggest that ESG-oriented investments demonstrated financial resilience during the pandemic, and incorporating ESG factors in investment policy allowed investors to manage portfolio risk better. The growing interest in ESG investing will likely continue in the post-pandemic era, driven by the development of ESG-focused investment products, regulatory support, and greater collaboration between investors and companies. However, data quality, consistency, and greenwashing challenges must be addressed to ensure the integrity and effectiveness of ESG investing in the future. Further research is recommended to deepen our understanding of ESG investing and its potential to contribute to a more resilient and sustainable global economy.